Theatre, finance and society in early modern England - Leinwand, Theodore B (Cambridge University Press, 2013)
This innovative study examines plays, historical narratives and biographical accounts, to discover how people coped with the exigencies of credit, debt, mortgaging and capital ventures in early modern England. Plays by Shakespeare and his contemporaries are paired with writings about the finances of royalty, aristocrats, privateers, theatrical entrepreneurs and debtors.